OC-022 Endoscopy Pitfalls in Celiac Disease Diagnosis; a Multicentre Study. (4th June 2013) - Rostami, K; Villanacci, M Rostami Nejad Vincenzo; Kollars, Sabine Hogg-; Volta, Umberto; Manenti, Stefania; Zali, Mohammad Reza; Caio, Giacomo; Giovenali, Paolo; Barakauskiene, Ausrine; Kazenaite, Edita; Becheanu, Gabriel; Diculescu, Mircea; et al.
Abstract : Introduction: The traditional diagnosis of celiac disease (CD) requires a small bowel biopsy to identify at histology the characteristic mucosal changes. The current biopsy practise among endoscopists for celiac disease is in most part unknown. The aims of this study were to compare the different diagnostic criteria in various centres in Italy, Iran, Lithuania, Romania and the UK, the methodological approach to the biopsy and to investigate the pitfalls of CD diagnosis. To measure the number of specimens submitted during duodenal biopsy among patients in Italy, Iran, Lithuania, Romania and the UK, and to determine the incremental diagnostic yield of adherence to the recommended number of specimens. Methods: A total of 931 patients who underwent duodenal biopsy for CD were recruited prospectively at nine centres in European and Middle East countries. Small-bowel biopsies were obtained from the duodenal bulb and the second part of the duodenum (and from the duodenal bulb when it had a micronodular appearance). The histopathological appearances were described according to the modified Marsh classification. Results: The most frequent degree of villous atrophy amongst Iranian subjects was 3A and that of the rest of the study population was 3C. The most common number of biopsy specimens for Romanian subjects was 1 (52%) followed by 2 for Iranian (56%), 3 for Lithuanian (66.7%) and British patients (65%) and 4 for Italian patients (48.3%). The main presenting symptom was anaemia (18.7%) followed by malabsorption (10.5%), diarrhoea (9.3%) and dyspepsia (8.2%). Conclusion: Taking less biopsy samples than recommended will have a negative impact in detecting massive number of undiagnosed cases. As CD is more common with atypical presentation, taking 4 duodenal biopsies is mandatory for an accurate diagnosis or its exclusion. Disclosure of Interest: None Declared